ESCRT components ISTL1 andLIP5 are required for tapetal function and pollen viability. Issue 8 (10th May 2021) - Goodman, Kaija; Paez-Valencia, Julio; Pennington, Janice; Sonntag, Annika; Ding, Xinxin; Lee, Han Nim; Ahlquist, Paul G.; Molina, Isabel; Otegui, Marisa S.
Abstract: Pollen wall assembly is crucial for pollen development and plant fertility. The durable biopolymer sporopollenin and the constituents of the tryphine coat are delivered to developing pollen grains by the highly coordinated secretory activity of the surrounding tapetal cells. The role of membrane trafficking in this process, however, is largely unknown. In this study, we used Arabidopsis thaliana to characterize the role of two late-acting endosomal sorting complex required for transport (ESCRT) components, ISTL1 and LIP5, in tapetal function. Plants lacking ISTL1 and LIP5 form pollen with aberrant exine patterns, leading to partial pollen lethality. We found that ISTL1 and LIP5 are required for exocytosis of plasma membrane and secreted proteins in the tapetal cells at the free microspore stage, contributing to pollen wall development and tryphine deposition. Whereas the ESCRT machinery is well known for its role in endosomal trafficking, the function of ISTL1 and LIP5 in exocytosis is not a typical ESCRT function. The istl1 lip5 double mutants also show reduced intralumenal vesicle concatenation in multivesicular endosomes in both tapetal cells and developing pollen grains as well as morphological defects in early endosomes/trans-Golgi networks, suggesting that late ESCRT components function in the early endosomal pathway and exocytosis. Abstract : Endosomal sorting complex required for transport proteins ISTL1 and LIP5 are required for exocytosis of both plasma membrane and secreted proteins in tapetal cells during microspore formation.